2011
DOI: 10.1111/j.1365-294x.2011.05181.x
|View full text |Cite
|
Sign up to set email alerts
|

DOG1 expression is predicted by the seed‐maturation environment and contributes to geographical variation in germination in Arabidopsis thaliana

Abstract: Seasonal germination timing of Arabidopsis thaliana strongly influences overall life history expression and is the target of intense natural selection. This seasonal germination timing depends strongly on the interaction between genetics and seasonal environments both before and after seed dispersal. DELAY OF GERMINATION 1 (DOG1) is the first gene that has been identified to be associated with natural variation in primary dormancy in A. thaliana. Here, we report interaccession variation in DOG1 expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
196
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(204 citation statements)
references
References 39 publications
(53 reference statements)
8
196
0
Order By: Relevance
“…An increase in seed dormancy levels by lower seed maturation temperatures could be important when Arabidopsis seeds mature in early spring or late autumn in temperate regions. Overall, our work confirms recent observations that DOG1 has an important role in the translation of seed maturation temperature to dormancy levels (Chiang et al, 2011;Footitt et al, 2011;Kendall et al, 2011). It will be of interest to find out whether DOG1 also plays a role in the influence on seed dormancy of other environmental conditions that occur during seed maturation, like light intensity, drought, daylength, and nitrate levels.…”
Section: Dog1 Protein Levels Predict the Dormancy Status Of Freshly Hsupporting
confidence: 77%
See 1 more Smart Citation
“…An increase in seed dormancy levels by lower seed maturation temperatures could be important when Arabidopsis seeds mature in early spring or late autumn in temperate regions. Overall, our work confirms recent observations that DOG1 has an important role in the translation of seed maturation temperature to dormancy levels (Chiang et al, 2011;Footitt et al, 2011;Kendall et al, 2011). It will be of interest to find out whether DOG1 also plays a role in the influence on seed dormancy of other environmental conditions that occur during seed maturation, like light intensity, drought, daylength, and nitrate levels.…”
Section: Dog1 Protein Levels Predict the Dormancy Status Of Freshly Hsupporting
confidence: 77%
“…In addition, it was shown that differences in DOG1 expression between Arabidopsis accessions contribute to geographical variation in dormancy and germination (Chiang et al, 2011). We confirmed the observation of Bentsink et al (2006) that the strongly dormant NIL DOG1 genotype shows higher DOG1 transcript levels than the low dormant Ler accession ( Figure 2A).…”
Section: Dog1 Expression and Protein Levels In Freshly Harvested Seedsupporting
confidence: 77%
“…However, as a major advance, we now know from ecological work with Arabidopsis (Huang et al, 2010;Moyers and Kane, 2010;Chiang et al, 2011;Barua et al, 2012;Kronholm et al, 2012) that natural genetic variation at the DOG1 locus is a major determinant for the local adaptation to novel environments, and we also know that the maternal environment controls DOG1 gene expression during seed maturation. For example, low temperature during seed maturation causes increased DOG1 gene expression and deeper primary dormancy of mature seeds (Chiang et al, 2011;Kendall et al, 2011;Nakabayashi et al, 2012). Arabidopsis, therefore, is a very good model also for addressing intraspecific questions in ecological, evolutionary, and developmental biology.…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%
“…Several recent publications clearly demonstrate that in Arabidopsis, QTLs with large effects on fitness colocalize with QTLs for field germination timing and seed dormancy (Huang et al, 2010;Moyers and Kane, 2010;Chiang et al, 2011;Barua et al, 2012;Kronholm et al, 2012). Germination phenology is under intense, geographically variable, natural selection in Arabidopsis, since it is the major determinant of fitness during the earliest stages of colonization (Huang et al, 2010;Moyers and Kane, 2010;Chiang et al, 2011;Barua et al, 2012;Kronholm et al, 2012). It is also evident that QTLs including DOG1 determine the phenotypic plasticity of seed germination/dormancy responses already on the mother plant in interaction with environmental factors such as seed maturation photoperiod and temperature.…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%
See 1 more Smart Citation